2016
DOI: 10.1111/jonm.12445
|View full text |Cite
|
Sign up to set email alerts
|

Nurses as family caregivers - barriers and enablers facing nurses caring for children, parents or both

Abstract: Increased awareness, support, flexibility and specific planning are required to retain nurses with family caregiving responsibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…Adults who are undertaking the triple caregiver roles, that is parenting and caring for an elderly member of the family, are part of the ‘sandwich generation’ (Gillett & Crisp, ). The results in the survey are in line with other studies in identifying feelings of guilt and the financial implications from having to reduce hours (Clendon & Walker, ). DePasquale et al () also identified perceived stress and psychological distress for staff who were double‐duty elder caregivers and poorer psychosocial functioning for those who were triple‐care givers, both of which were identified by several of the CFHN in the study.…”
Section: Discussionsupporting
confidence: 87%
“…Adults who are undertaking the triple caregiver roles, that is parenting and caring for an elderly member of the family, are part of the ‘sandwich generation’ (Gillett & Crisp, ). The results in the survey are in line with other studies in identifying feelings of guilt and the financial implications from having to reduce hours (Clendon & Walker, ). DePasquale et al () also identified perceived stress and psychological distress for staff who were double‐duty elder caregivers and poorer psychosocial functioning for those who were triple‐care givers, both of which were identified by several of the CFHN in the study.…”
Section: Discussionsupporting
confidence: 87%
“…It is difficult for nurses to balance work and life because they are not provided with adequate resources to buffer job demands such as inflexible shift work schedule and mandatory night duty. This finding was consistent with the findings from other countries in which previous studies (Clendon, 2018) reported that workplace childcare services should accommodate shift schedule hours, and flexible work shifts with time off would need to be guaranteed so that nurses can engage with their family and professional improvement activities.…”
Section: Suggestions For Reducing Mistreatment Of Nursessupporting
confidence: 91%
“…While a supportive work environment that values and nurtures all nurses/midwives is required for retention (Chenoweth, Merlyn, Yun‐Hee, Tait, & Duffield, 2013), there is an urgent need to review supportive structures that can help retain this cohort in the public health care system. For example, targeted supports such as providing flexible and part‐time working arrangements (Clendon & Walker, 2016) and support with childcare availability (Clendon & Walker, 2016) are recommended. Lartey, Cummings, and Profetto‐McGrath (2014) in a systematic review of retention strategies for experienced registered nurses identified orientation and mentoring as the most effective strategies in addressing retention.…”
Section: Discussionmentioning
confidence: 99%